2019
DOI: 10.1038/s41598-019-47458-0
|View full text |Cite
|
Sign up to set email alerts
|

Tinospora cordifolia protects against inflammation associated anemia by modulating inflammatory cytokines and hepcidin expression in male Wistar rats

Abstract: Systemic iron homeostasis dysregulation is primarily associated with inflammation- associated anemia (AI) due to hepcidin up-regulation. Tinospora cordifolia (TC) has shown remarkable anti-inflammatory properties and has been found useful in the treatment of inflammatory disorders. However, the effects and mechanisms of TC on AI have not been studied yet. We conducted in vivo and in vitro studies to evaluate the effect of TC on AI. HPLC studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Furthermore, the aqueous extract of T. cordifolia was also reported to be significantly reduced the production of NO and downregulated gene expression of TNF-α and COX-2. Besides this, the extract also inhibited the gene expression of toll-like receptor 4 [60], which is an important regulator of wound inflammation [61]. However, the aqueous extract of T. cordifolia only significantly inhibited IL-β at higher concentrations of 250-500 μg/ml.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, the aqueous extract of T. cordifolia was also reported to be significantly reduced the production of NO and downregulated gene expression of TNF-α and COX-2. Besides this, the extract also inhibited the gene expression of toll-like receptor 4 [60], which is an important regulator of wound inflammation [61]. However, the aqueous extract of T. cordifolia only significantly inhibited IL-β at higher concentrations of 250-500 μg/ml.…”
Section: Discussionmentioning
confidence: 94%
“…Active components of WS (withanone and withaferin A) and AR (shatavarin-IV) also inhibited production of IL-6 in in vitro system. It has also been reported that aqueous extract of TC protects against in ammation associated anaemia by modulating hepcidin expression, IL-6 and other pro-in ammatory cytokine cascade 63 .There is a clinical evidence of COVID-19 from Wuhan, China indicating that the immunocompromised patients are at high risk of developing fatal respiratory syndrome 71 . In view of this, immunomodulating drugs are being considered bene cial for COVID-19 management 72 .…”
Section: Discussionmentioning
confidence: 99%
“…This was supported by clinical observations of reduction in haemoglobin and increased erythrocyte sedimentation rate. This induces hypoxia leading to organ failure 62 .A systematic in vivo study of TC extract showed signi cant increase in levels of haemoglobin and erythrocyte count to maintain systemic iron homeostasis 63 . WS showed prophylactic effect in pulmonary hypertension characterised by hypoxia and in ammation 64 .…”
Section: Discussionmentioning
confidence: 99%
“…NS seed oil suppressed the viral burden to undetectable levels within ten days of intraperitoneal (i.p.) injection of black seed oil in a murine model [ 136 ].…”
Section: Herbs Considered Usable For the Treatment Of Covid-19mentioning
confidence: 99%
“…The strongest candidates for COVID-19 treatment thus appear to be nigellidine and α-hederin. Further studies are needed to confirm the medical value of Nigella sativa and to advocate its usage as a preventative measure against coronavirus infection [ 136 ].…”
Section: Herbs Considered Usable For the Treatment Of Covid-19mentioning
confidence: 99%